Some Tasks Resulting in Differential Equations - Baymuratova Klara Amangeldievna (International Journal on Human-Computing Studies, 2022)
In this paper, problems are presented, the solution of which leads to differential equations. These tasks show that differential equations are an effective mathematical apparatus through which the main tasks of natural science are realized.